Om felaktiga särskrivningar i svenskan och norskan och om ordboksbaserade och statistiska program för att hitta dem - Malmgren, Sven-Göran; Vadtvedt Fjeld, Ruth (Nordiske Studier i Leksikografi, 2006)
On decomposed compounds in Swedish and Norwegian and Dictionary-based and statistical programs to detect them. In written Swedish and Norwegian, as well as in Danish, there is a tendency to decompose compounds, e.g. barn bok instead of, correctly, barnbok (‘children’s book’). The article deals with several aspects of this phenomenon, in particular the possibilities of detecting them by means of dictionary-based and statistical programs. It is claimed that statistical (and non-linguistic) programs should, at most, be regarded as complements to dictionary- based ones. Intelligent programs must also be based on morphological analysis of the (potential) compounds. As for Norwegian, an extensive corpus investigation indicates that decomposition of compounds is much more common in informal texts than in formal ones.